If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -2r = 9 + -1r Solving 1 + -2r = 9 + -1r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 'r' to each side of the equation. 1 + -2r + r = 9 + -1r + r Combine like terms: -2r + r = -1r 1 + -1r = 9 + -1r + r Combine like terms: -1r + r = 0 1 + -1r = 9 + 0 1 + -1r = 9 Add '-1' to each side of the equation. 1 + -1 + -1r = 9 + -1 Combine like terms: 1 + -1 = 0 0 + -1r = 9 + -1 -1r = 9 + -1 Combine like terms: 9 + -1 = 8 -1r = 8 Divide each side by '-1'. r = -8 Simplifying r = -8
| 12x^4-26x^3+10x^2=0 | | 9x-2=9(x+8) | | 8=6-p(p+3) | | 2x(6x^3-13x^2+5x)=0 | | 8y^3+6y^2-9y= | | 5(32n-40)=4(5n+1) | | x=2(1-x) | | p+12=-5 | | 22x+3x^2=-40 | | 5x+7=5(X+2) | | (4x+9)+(3x-12)+2x=180 | | 3k-12=2k+10 | | 46x-14x^2-12=0 | | 2(q)+5(1-q)=6q+1(1-q) | | 2p-17=2(p-3)+9 | | 3x^2+22x+40=0 | | 6(5-4x)=-18 | | -7x^2+14x=x | | x(x)+4x=32 | | -3(3+5x)=96 | | 4x^2+4x+1=5 | | -7x^2+14x=y | | 0.18(y-7)+0.04y=0.12y-1.4 | | 4(p)+3(1-p)=3p+7(1-p) | | 0.5v+4.3=2.3 | | -2x-2x-5=5x-2+6 | | 3x^2+12x=y | | (x+4)=5+(5+40) | | v^2+6.1v-6=0 | | 5(4-7x)=405 | | x^2+5x=y | | 9x-4=4x-29 |